Can dose outside the PTV influence the risk of distant metastases in stage I lung cancer patients treated with stereotactic body radiotherapy (SBRT)?. Issue 3 (September 2018) - Diamant, André; Chatterjee, Avishek; Faria, Sergio; Naqa, Issam El; Bahig, Houda; Filion, Edith; Robinson, Cliff; Al-Halabi, Hani; Seuntjens, Jan
Abstract: Background and purpose: In an era where little is known about the "abscopal" (out-of-the-field) effects of lung SBRT, we investigated correlations between the radiation dose proximally outside the PTV and the risk of cancer recurrence after SBRT in patients with primary stage I non-small cell lung cancer (NSCLC). Materials and methods: This study included 217 stage I NSCLC patients across 2 institutions who received SBRT. Correlations between clinical and dosimetric factors were investigated. The clinical factors considered were distant metastasis (DM), loco-regional control (LRC) and radiation pneumonitis (RP). The dose (converted to EQD2) delivered to regions of varying size directly outside of the PTV was computed. For each feature, area under the curve (AUC) and odds ratios with respect to the outcome parameters DM, LRC and RP were estimated; Kaplan–Meier (KM) analysis was also performed. Results: Thirty-seven (17%) patients developed DM after a median follow-up of 24 months. It was found that the mean dose delivered to a shell-shaped region of thickness 30 mm outside the PTV had an AUC of 0.82. Two years after treatment completion, the rate of DM in patients where the mean dose delivered to this region was higher than 20.8 Gy2 was 5% compared to 60% in those who received a dose lower than 20.8 Gy2 . KM analysis resulted in a hazard ratio of 24.2 (95% CI: 10.7, 54.4); p < 10 −5 . No correlations were found between any factor and either LRC or RP. Conclusions: The results of this study suggest that the dose received by the region close to the PTV has a significant impact on the risk of distant metastases in stage I NSCLC patients treated with SBRT. If these results are independently confirmed, caution should be taken, particularly when a treatment plan results in a steep dose gradient extending outwards from the PTV.